(untitled) (Research, Society and Development, 2024)
Objective: to analyze diseases of the eyes and appendages in the elderly population, seeking possible justifications for such data. Methods: This is an epidemiological, ecological, descriptive and retrospective study, which analyzes data from DATASUS, from 2013 to 2023, in relation to international standards relating to diseases of the eyes and appendages in a population aged over 60 years. Results: The work shows a high prevalence of Cataracts in Brazil, with approximately 92.8% of hospitalizations among the elderly population, followed by Glaucoma with 6.8%. In relation to regions, the Southeast has the highest number of cases of hospitalizations due to diseases of the eyes and appendages. Conclusion: There was a drop in the number of internationals in 2020 and 2021 generated by the Covid-19 pandemic.